Numerical Simulation of the Collector Angle Effect on the Performance of the Solar Chimney Power Plant - Al-Taaie, Arkan K.; Mohammad, Waheeds S.; Jubear, Abbas J. (Al-Khwarizmi Engineering Journal, 2017)
Sloped solar chimney system is a solar chimney power plant with a sloped collector. Practically, the sloped collector can function as a chimney, then the chimney height can be reduced and the construction cost would be reduced.The continuity, Naver-stockes, energy and radiation transfer equations have been solved and carried out by Fluent software. The governing equations are solved for incompressible, 3-D, steady, turbulent standard model with Boussiuesq approximation  to develop for the sloped solar chimney system in this study and evaluate the performance of solar chimney power plant  in Baghdad city of Iraq numerically by Fluent (14) software with orking conditions such as solar radiation intensity (300,450,600,750 and 900 W/m2), and collector which angle (0°, 15° and 30°).The results show that the change of collector angle has considerable effects on the performance of the system.The velocity increases when the collector angle increases and reach to the maximize  value at a collector angle (30°). The temperature increase with the collector tile angle increase at solar intensity times (7:30,8:15,9,10 AM) but decrease at 12:30 PM) corresponding to solar intensitIes. The study show that Iraqi wather are suitable for this system.